Knowledge Management Online Application in PDAM Lampung Province - Putra, Arie Setya; Febriani, Ochi Marshella (Prosiding International conference on Information Technology and Business (ICITB), 2017)
The development of this technology is very fast, one of the media that utilizes technology such as knowledge management application is media for documentation of knowledge and facilities that can support knowledge sharing culture in PDAM Lampung. The use of interactive online knowledge management can facilitate the companys activities to achieve the project objectives. The utilization of this technology connects computerized technology with the application of appropriate system development methods in order to make the information-sharing relationships of enterprise activities can be stored and well controlled. By applying the first 7 step method described in prototype design the knowledge management application is expected to facilitate the implementation of research and other development support methods such as waterfall method. The use of knowledge stored in the knowledge database, is expected to add new knowledge to users in business processes, the operation of computer applications, monitoring, or how to solve cases encountered in corporate projectsÂ Key word : Knowledge Management Application, Prototype and waterfall, PDAM